Relationship of Marketing Mix to Patient Perception At the Mapilli Community Health Center, Polewali Mandar Regency - T, Andriani; Masriadi, Masriadi; Ahri, Reza Aril; Yusriani, Yusriani; A. Fachrin, Suharni; Batara, Andi Surahman (JURNAL PROTEKSI KESEHATAN, 2024)
The marketing mix is ​​a series of marketing tools that a company (in this case a hospital or health center) uses continuously to achieve its marketing goals in the target market. With the Marketing Mix, the hospital or Community Health Center will be able to develop broader and specific marketing activities for the hospital or Community Health Center because in more detail, the efforts made will be clearer and more focused. Perception is the process used by an individual to select, organize and interpret information input to create a meaningful picture of the world. The decisions taken in the management process will determine marketing success. The process must be considered so that each part can work according to the SOP. By improving health services in marketing, patient assessment will increase. Results: The marketing mix (Product) has a significant relationship with patient perceptions (p-value of 0.042), the marketing mix (Price and Place) has a relationship but is not significant with patient perceptions. Conclusion: There is a significant relationship between product marketing mix and patient perception and there is no significant relationship between price and place marketing mix and patient perception.